DNA methylation changes associated with Parkinson's disease progression: outcomes from the first longitudinal genome-wide methylation analysis in blood. Issue 4 (3rd April 2019) - Henderson-Smith, Adrienne; Fisch, Kathleen M.; Hua, Jianping; Liu, Ganqiang; Ricciardelli, Eugenia; Jepsen, Kristen; Huentelman, Mathew; Stalberg, Gabriel; Edland, Steven D.; Scherzer, Clemens R.; Dunckley, Travis; Desplats, Paula
ABSTRACT: Parkinson's Disease (PD) is a common neurodegenerative disorder currently diagnosed based on the presentation of characteristic movement symptoms. Unfortunately, patients exhibiting these symptoms have already undergone significant dopaminergic neuronal loss. Earlier diagnosis, aided by molecular biomarkers specific to PD, would improve overall patient care. Epigenetic mechanisms, which are modified by both environment and disease pathophysiology, are emerging as important components of neurodegeneration. Alterations to the PD methylome have been reported in epigenome-wide association studies. However, the extent to which methylation changes correlate with disease progression has not yet been reported; nor the degree to which methylation is affected by PD medication. We performed a longitudinal genome-wide methylation study surveying ~850, 000 CpG sites in whole blood from 189 well-characterized PD patients and 191 control individuals obtained at baseline and at a follow-up visit ~2 y later. We identified distinct patterns of methylation in PD cases versus controls. Importantly, we identified genomic sites where methylation changes longitudinally as the disease progresses. Moreover, we identified methylation changes associated with PD pathology through the analysis of PD cases that were not exposed to anti-parkinsonian therapy. In addition, we identified methylation sites modulated by exposure to dopamine replacement drugs. These results indicate that DNA methylation is dynamic in PD and changes over time during disease progression. To the best of our knowledge, this is the first longitudinal epigenome-wide methylation analysis for Parkinson's disease and reveals changes associated with disease progression and in response to dopaminergic medications in the blood methylome.